ANALISIS BUDAYA KERJA RUMAH SAKIT ISLAM DI MALANG - Asfiah, Nurul (Journal of Innovation in Business and Economics, 2010)
The respondents are the whole of medical, administrative and paramedical employees. This research uses descriptive qualitative analysis, mean technique, followed by clustering technique to determine dominant values which are used at the hospital based on Islamic values. The method of data collection is anquette, interview, and documentation. Pursuant to from this result is obtained, hence will identify work cultural that is in the form of dominant values formula, that is creative and innovative, competitiveness, responsibility and loyal, personality, warmness and focus, and  difference and synergy.